Masjid Agung Banten: Jejak Akulturasi Budaya dan Objek Wisata Religi - Juliawati, Rini; Ahmad Pramuja, Rido; Da’imah, Syaripatu; Arsiadi; Rahman Hamid, Abd; Mahfuddin Setiawan, Agus (TARIKHUNA: JURNAL SEJARAH PERADABAN ISLAM, 2025)
This research aims to examine the representation of cultural acculturation in the architecture of the Great Mosque of Banten and the surrounding buildings, which reflect the fusion of various cultures, such as Islam, Hinduism, Java, China, and Europe. The method used is the historical research method, which includes the stages of heuristics, source criticism, interpretation, and historiography. The results showed that the Great Mosque of Banten not only functioned as a center for the spread of Islam, but also as a symbol of the power of the Banten Sultanate. Its architecture reflects the fusion of cultures across civilizations, which can be seen through elements such as the European-style tower that resembles a lighthouse, the multilevel roof structure typical of traditional Javanese architecture, and ornaments that show Chinese and Hindu influences. In addition to its religious function, the presence of the tombs of the Banten Sultans in the mosque complex also makes this place a center of pilgrimage activities and religious tourism destinations. This contributes to the social and economic dynamics of the local community. Thus, it can be concluded that the Great Mosque of Banten is a historical manifestation of cultural and religious acculturation in the context of Nusantara Islamic architecture. Keywords: Banten Sultanate, Great Mosque of Banten, cultural acculturation, Pilgrimage.